2014
DOI: 10.18632/oncotarget.2284
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of KRAS-Mutant cells by miR-126 through repression of multiple genes essential for the survival of KRAS-Mutant cells

Abstract: MicroRNAs (miRNAs) regulate the expression of hundreds of genes. However, identifying the critical targets within a miRNA-regulated gene network is challenging. One approach is to identify miRNAs that exert a context-dependent effect, followed by expression profiling to determine how specific targets contribute to this selective effect. In this study, we performed miRNA mimic screens in isogenic KRAS-Wild-type (WT) and KRAS-Mutant colorectal cancer (CRC) cell lines to identify miRNAs selectively targeting KRAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Similarly, MIR126 was found to suppress tumours by directly targeting the insulin receptor substrate-1 (IRS1) [1214] and the disintegrin- and metalloproteinase domain-containing protein-9 (ADAM9) [15]. Using luciferase assay, it was found that MIR126 targets other factors, such as SOX2, SLC7A5, EGFL7 and VEGF [1620]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, MIR126 was found to suppress tumours by directly targeting the insulin receptor substrate-1 (IRS1) [1214] and the disintegrin- and metalloproteinase domain-containing protein-9 (ADAM9) [15]. Using luciferase assay, it was found that MIR126 targets other factors, such as SOX2, SLC7A5, EGFL7 and VEGF [1620]. …”
Section: Introductionmentioning
confidence: 99%
“…The expression of miR-126 and its host gene was reduced in most cancers with a high frequency of KRAS mutations including lung cancer (36). A subset of miR-126-regulated genes selectively required for the survival and clonogenicity of KRAS-Mutant cells have been identified, supporting the role of miR-126 in tumor formation and progression (37).…”
Section: Discussionmentioning
confidence: 81%
“…This is also true for miRNA-126 and the regulation of several of these mRNA targets may all impact on the risk of disease recurrence from local colon cancer. Some of the more well described targets are SPRED1, p85β, and PI3KR2 governing vascular integrity [10,27] , VEGF-A regulating AKT-pathway signaling [28] , CXCR4 and IRS-1 involved in CRC cell proliferation and migration [29,30] , and KRAS impacting on the viability of the mutated tumor cells [31] . Recent reviews have also highlighted the clinical potential of miRNA-126 [32][33][34] .…”
Section: Discussionmentioning
confidence: 99%